Features of Polycystic Kidney Disease Course in Children: Literature Data and Description of a Clinical Case - I.S. Lembryk; L.Ya. Ivanyshyn; I.V. Shlimkevich; S.I. Yakymiv (Zaslavsky O.Yu., 2012)
The article deals with features of polycystic kidney disease course at the present stage according to literature data and results of own clinical studies. It was proved that autosomal recessive polycystic kidney disease has the most unfavorable prognosis: it could manifest soon after birth and often leads to death in early childhood. Diagnostics of the disease is difficult and includes genetic consultation and complex examination of main clinical and instrumental indexes. The main in treatment is adequate renoprotective and anticytokine therapy, and also the hemodialysis.